Development of 3D-printed droplet networks as a platform to build functional synthetic tissues - Alcinesio, A (2019)
The development of synthetic multicellular systems that can mimic complex cooperative behaviour of living tissues represents a major challenge for bottom-up synthetic biology. Tissue-like systems would allow the design of devices and materials that can communicate with living tissues and monitor, control or complement their biological activity. Networks of 3D-printed aqueous droplets in oil joined by droplet interface bilayers (DIBs) represent a powerful platform from which soft-electronic devices and synthetic tissues have been developed. Precise control of droplet packing to produce constructs with predictable 3D architectures, assembly of functional constructs of dimensions relevant to biomedical applications, and transfer of functional constructs to aqueous environment will enable design of increasingly sophisticated systems. Here, we achieve highly regular droplet packing in 3D-printed synthetic tissues by controlling the equilibrium contact angle θDIB at the droplet-droplet interface. As a result, we fabricate synthetic tissues with single-droplet precision in three dimensions. We also build larger and modular synthetic tissues by assembling building blocks constructed independently. Lastly, we employ a novel strategy to transfer 3D-printed droplet networks to aqueous bulk phase, forming a functional lipid bilayer at the interface with the aqueous bulk while retaining the architecture and the functionality of the internal lipid bilayers. Using this method, we generate synthetic tissues that can communicate with their environment, as a fundamental step towards interface with living tissues in physiological conditions.